Groundwater Quality Impacts on the Soils of Two Sites, NW Mosul, Iraq (Iraqi National Journal of Earth Science (INJES), 2026)
This study evaluates the quality of groundwater from wells located in two areas on both sides of the Tigris River northwest of Mosul City in order to conduct a hydrochemical comparison and assess their impact on soil salinity. A total of 10 groundwater samples were collected from area (A), and 9 samples from area (B). Additionally, irrigated soil samples were taken from each well, along with three naturally rain-fed soil samples from each area. The water analyses include measurements of electrical conductivity (EC), pH, total hardness, and the major cations and anions. Soil analyses include salinity, pH, calcium carbonate content, and soil texture. The EC values of groundwater range from 3.51 to 7.49 dS/m in area (A), and from 1.02 to 5.23 dS/m in area (B). The average concentrations of salinity, sodium, potassium, calcium, sulfates, and chlorides in area (A) are approximately 1.5 times higher than those in area (B). The impact of irrigation with well water on soil is evident, as most irrigated soils in area (A) are saline soil. In contrast, only one saline soil sample is recorded in area (B). This difference is attributed to the lower salinity levels of well water in area (B). Long-term use of high-salinity groundwater in area (A) has led to soil salinization, especially when compared to rain-fed soils. Saturation indices for calcite, dolomite, gypsum, and halite minerals present in the aquifer are also calculated. Furthermore, hierarchical cluster analysis is applied to classify the wells in both areas.
Keywords: Ground water, Water quality, Aquifer, Soil salinity, Irrigation.